2001
DOI: 10.1542/peds.108.4.856
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Multiple Antibiotic Resistance inStreptococcus pneumoniaeFrom Healthy Children Living in Isolated Rural Communities: Association With Cephalosporin Use and Intrafamilial Transmission

Abstract: Young age and intrafamilial transmission were important risk factors for carriage of both susceptible and resistant S pneumoniae. In contrast, previous cephalosporin use was linked specifically to resistant pneumococcal carriage, which suggests that modifications in antibiotic usage patterns may have salutary effects on antimicrobial resistance. These results extend previous observations in large cities regarding the penetration of multiple-drug-resistant clones of pneumococci into community populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(61 citation statements)
references
References 54 publications
3
57
1
Order By: Relevance
“…Specimens for this analysis were obtained from children in 16 noncontiguous communities, some of which are more densely populated than some regions previously studied. 13,17,18 The variability seen here by community in the fraction of S pneumoniae nonsusceptible to penicillin (0%-58%) partly reflects the small number of isolates from some communities but has also been seen in a study of French schools. 37 However, when we used multivariate techniques to examine the degree of variability observed, we found that it did not exceed what would be expected by chance.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Specimens for this analysis were obtained from children in 16 noncontiguous communities, some of which are more densely populated than some regions previously studied. 13,17,18 The variability seen here by community in the fraction of S pneumoniae nonsusceptible to penicillin (0%-58%) partly reflects the small number of isolates from some communities but has also been seen in a study of French schools. 37 However, when we used multivariate techniques to examine the degree of variability observed, we found that it did not exceed what would be expected by chance.…”
Section: Discussionmentioning
confidence: 50%
“…9,36 Although the high prevalence of penicillin-resistant strains (MIC Ն2) is similar to that reported from some areas, 10,12 it far exceeds that found in most studies. 11,13,17 The variability in these reports is not surprising because most reflected a single geographic area. Specimens for this analysis were obtained from children in 16 noncontiguous communities, some of which are more densely populated than some regions previously studied.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Soon after, resistance rates to different antimicrobial agents among S. pneumoniae strains increased disturbingly and they have become a worldwide problem [13]. The carriage prevalence of resistant strains has also extended and this has amplified the issue [14,15]. Furthermore, S. pneumoniae has intrinsic resistance to a large group of antibiotics, including polypeptides, aminoglycosides and first-generation quinolones [16].…”
Section: Mechanisms Of Resistance In Streptococcus Pneumoniaementioning
confidence: 99%
“…5 The volume of antimicrobial use is the main factor in the development of resistance 6,7 both in individuals 8 and populations. 9,10 In populations with heavy use, the risk of carrying resistant organisms caused by household members' use of antibiotics, 11 intrafamilial transmission, 12,13 or proximity to an antibiotics source 14 often outweighs the risk of personal antibiotics use.…”
Section: Introductionmentioning
confidence: 99%